2018
DOI: 10.1016/j.bbmt.2018.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic Hematopoietic Stem Cell Transplantation for GATA2 Deficiency Using a Busulfan-Based Regimen

Abstract: Allogeneic hematopoietic stem cell transplantation (HSCT) reverses the bone marrow failure syndrome due to GATA2 deficiency. The intensity of conditioning required to achieve reliable engraftment and prevent relapse remains unclear. Here, we describe the results of a prospective study of HSCT in 22 patients with GATA2 deficiency using a busulfan-based conditioning regimen. The study included 2 matched related donor (MRD) recipients, 13 matched unrelated donor (URD) recipients, and 7 haploidentical related dono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
69
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 20 publications
3
69
3
1
Order By: Relevance
“…The ability of unconditioned DLI to improve mixed chimerism after BMT may ultimately be low, but data presented here and by others suggest that mixed chimerism may not require intervention with DLI, given that it can be stable over time and sufficient for phenotype reversal for some PIDs [23,24,27,32]. Although PTCy is known to decrease chronic GVHD incidence effectively, including in PID patients [23,25,[33][34][35], the complete absence of chronic GVHD in this study, confirmed on serial, comprehensive evaluations, is one of the most clinically important and promising findings. The low incidence of severe acute and chronic GVHD may be partly related to the gradual increase in donor T cells noted in most patients, allowing for early mixed chimerism, which may be tolerogenic.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The ability of unconditioned DLI to improve mixed chimerism after BMT may ultimately be low, but data presented here and by others suggest that mixed chimerism may not require intervention with DLI, given that it can be stable over time and sufficient for phenotype reversal for some PIDs [23,24,27,32]. Although PTCy is known to decrease chronic GVHD incidence effectively, including in PID patients [23,25,[33][34][35], the complete absence of chronic GVHD in this study, confirmed on serial, comprehensive evaluations, is one of the most clinically important and promising findings. The low incidence of severe acute and chronic GVHD may be partly related to the gradual increase in donor T cells noted in most patients, allowing for early mixed chimerism, which may be tolerogenic.…”
Section: Discussionmentioning
confidence: 74%
“…At present, there are no published PTCy-based haplo transplant approaches for patients with PID that similarly avoid serotherapy, radiation, and/or myeloablation for direct comparison to this platform. Approaches that do include 1 or more of these factors have resulted in high engraftment rates with haplo donors in patients with PID [23,35,40,41]. Regardless, further improving engraftment without sacrificing the favorable aspects of this platform is desirable.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, patients in whom a bone marrow clone has a proliferative advantage may need a more intensive conditioning regimen to eradicate that clone (Hickstein, ). Finally, the administration of PTCy after HSCT with matched (un)related donors has recently shown promising results in terms of reducing the severity of both acute and chronic GVHD, and is now being evaluated in the context of GATA2 deficiency (Parta et al , ; McCurdy et al , ). Prospective multicentre studies are recommended to further optimise HSCT in GATA2‐deficient patients.…”
Section: Transplant Characteristicsmentioning
confidence: 99%
“…The onset of clinical symptoms spans from infancy to late adulthood, with most patients presenting in adolescent and early adult years. The only curative treatment is allogeneic HSC transplantation (allo-HSCT), which can reverse the haematological, immunological and pulmonary manifestations (Parta et al, 2018). Although recent advances have led to a better knowledge of this syndrome, many issues still need to be addressed (McReynolds et al, 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation